A comprehensive analytical description of the asymmetric active snubber. Issue 1 (18th August 2022) - Schlüter, Michael; Pfost, Martin
Abstract: Power modules for several hundred amperes suffer from a high stray inductance compared to discrete setups at similar current density. The use of silicon carbide in such modules is beneficial but due to the high stray inductance, the switching speed must be reduced to keep the voltage overshoot below breakdown voltage. As a result, the semiconductor material cannot be fully utilised. To improve the utilisation in terms of power output, by strong over‐voltage reduction, reduced ringing, and highest switching speeds an asymmetric active snubber was introduced. This work targets an improved understanding of the active snubber by deriving analytical models to describe the behaviour during turn‐on and turn‐off and elaborate optimisation opportunities. The models are compared to measurements for validation and an improved loss estimation is derived as well as a prediction of the snubber voltage. Different modes of operation are investigated and compared to a similar DC‐snubber setup. Finally, the model is used to pre‐calculate the timing for optimal operation.